Teach Yourself VISUALLY HTML and CSS - Hart-Davis, Guy (Teach Yourself VISUALLY (Tech) Series., 2023)
Level-up your HTML and CSS web development skills with this dynamic, visual guide Teach Yourself VISUALLY HTML and CSS is the perfect resource for those of you who prefer to learn visually and would rather be shown how to do something - with crystal-clear screenshots and easy explanations - than suffer through long-winded explanations. You'll find step-by-step walkthroughs showing you how to tackle over 120 individual tasks involving HTML and CSS. Each task-based spread covers a single technique, ensuring you learn first the basics and then more advanced topics one straightforward piece at a time. You'll learn to write HTML code in a text editor or an integrated development environment, add and format text, prepare images for the web, insert links to other pages, control layout with style sheets, add JavaScript to a web page, and more. You'll also discover how to: Create websites that look great in 2023 and beyond with classic HTML and skills and the most modern tips and tricks for contemporary web coding Optimize your websites for performance and speed, ensuring every visitor gets the best possible experience Add modern elements to your code, including , , , and , and make your code accessible to as many people as possible Teach Yourself VISUALLY HTML and CSS is your personal roadmap to understanding how to get the most out of HTML and CSS to create, format, and troubleshoot websites of all kinds. This book will get you to the next level of web development, quickly and easily.